2014
DOI: 10.1142/s0219519414500705
|View full text |Cite
|
Sign up to set email alerts
|

Gait Patterns After Posterior Cruciate Ligament Injury: A Comparison of Symptomatic and Asymptomatic Patients

Abstract: This study examined chronic, isolated posterior cruciate ligament (PCL) rupture patients, dividing them into symptomatic and asymptomatic groups according to whether they displayed obvious symptoms in daily activities. Each group comprised 10 patients while 10 healthy, young individuals were adopted as the control group. Using a three-dimensional motion analysis system and force plates, the gait patterns of the PCL-deficient patients were analyzed from both kinematics and kinetics perspectives to identify whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our results showed that during the terminal stance phase, extension moments were significantly smaller in the involved leg of the PCL-d group than in the uninvolved leg of the PCL-d group, which may decrease force and prevent the tibia from posterior translation during the extension movement. The study of Liu et al 28 showed that the asymptomatic PCL-deficient knee had smaller extension moments in the terminal stance than those seen in a control group, while the values of the symptomatic PCL-deficient group were closer to those of healthy participants. In our study, patients in the PCL-d group had no symptoms during level walking; therefore, knee extension deficiency could be a result of the adaptive gait pattern after a PCL rupture.…”
Section: Knee Kineticsmentioning
confidence: 85%
See 2 more Smart Citations
“…Our results showed that during the terminal stance phase, extension moments were significantly smaller in the involved leg of the PCL-d group than in the uninvolved leg of the PCL-d group, which may decrease force and prevent the tibia from posterior translation during the extension movement. The study of Liu et al 28 showed that the asymptomatic PCL-deficient knee had smaller extension moments in the terminal stance than those seen in a control group, while the values of the symptomatic PCL-deficient group were closer to those of healthy participants. In our study, patients in the PCL-d group had no symptoms during level walking; therefore, knee extension deficiency could be a result of the adaptive gait pattern after a PCL rupture.…”
Section: Knee Kineticsmentioning
confidence: 85%
“…Most previous studies 9,11,16,28 regarding PCL ruptures have focused on knee kinematics in the sagittal plane of the PCL-deficient leg during the stance phase of walking and found no significant difference among the involved leg of the PCL-d group, the uninvolved leg of the PCL-d group, and a control group. Our study not only focused on the knee kinematics and kinetics of legs in the PCL-d group in 3D planes but also on the hip and ankle in 3D planes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation